2016
DOI: 10.1177/1934578x1601101118
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Methyl Ester Composition of Some Turkish Apiaceae Seed Oils: New Sources for Petroselinic Acid

Abstract: The seed oils of twenty-six species of Apiaceae belonging to the genera Bunium,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…The difference may be due to the filling rate of the seeds of the species as well as ecological conditions. Our results on the main components of the oil were similar to previous studies reported by different researchers, which consisted of petroselinic, linoleic, and palmitic acids (Placek, 1963;Kleiman and Spencer, 1982;Bagci, 2007;Kucukboyaci et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The difference may be due to the filling rate of the seeds of the species as well as ecological conditions. Our results on the main components of the oil were similar to previous studies reported by different researchers, which consisted of petroselinic, linoleic, and palmitic acids (Placek, 1963;Kleiman and Spencer, 1982;Bagci, 2007;Kucukboyaci et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…While Keiman and Spencer (1982) determined the oil ratio of the species as 8.6% in studies as interest in H. cristatum, Kucukboyaci et al (2016) reported that the fruits of the species contain 15.8% fatty oil. Similar to our results with the researchers, the studies on the oil content of the species found palmitic acid (4.3-7.1%), linoleic acid (13.2-19.8%), oleic acid (4.2-74.84%), and petroselinic acid (54.4-72.2) as important components of the oil (Kleiman & Spencer, 1982;Ozturk et al, 2014;Kucukboyaci et al, 2016). Kleiman and Spencer (1982) determined the oil rate of H. microcarpum as 14.1% and reported that the main components were 15.0% palmitic acid, 6.5% petroselinic acid, 20.5% oleic acid, 37.8% linoleic acid.…”
Section: Discussionmentioning
confidence: 99%
“…It is noticeable that the majority of them are from Turkey (33%) and Italy (27%), followed by Spain (9%), Iran (9%), Serbia (8%), and Algeria (7%). Turkey has the highest Apiaceae diversity in Asian countries and probably in the world, with about 150 species in 42 genera [ 12 , 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Petroselinic acid was found to be the major fatty acid present in the seed oils of C. cristata (72.2%). Linoleic acid was instead the most abundant component of C. microcarpos seed oil (36.9%) [ 13 ].…”
Section: Phytochemical Constituentsmentioning
confidence: 99%
“…Among the endemic Ferulago species, F. longistylis was found to have limited studies on its phytochemicals and activities [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%